Kaedah mudah pengekstrakan propolis kelulut - Ibrahim, Muhammad; Abd Rani, Nurlisa Fatihah; Yahya Abker, Hagar Abdullah (2021)
“Kaedah Mudah Pengekstrakan Propolis Kelulut” describes brief descriptions of five main chapters; starting from the (1) Introduction of Trigona spp. Propolis (2) Benefit of the propolis (3) Methods of Trigona spp. Propolis Extraction (4) Storage Method (5) Uses in the Nutraceutical and Functional Foods Industries. This disclosure also emphasizes the novelty of the research outcome regarding the optimized extraction conditions by using response surface methodology (RSM) for the Malaysian Aqueous extract of Trigona spp.Propolis